2020
DOI: 10.1108/jsocm-11-2018-0136
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability endeavors and sustainable development in Spanish public hospitals

Abstract: Purpose The research aims to describe the foundation of healthcare organizations’ past and present sustainability endeavors; describe the direction of a health-care organizations’ sustainable development; reveal and characterize what determines the foundation and direction in a public health-care sector; and provide some insights into social marketing for sustainability endeavors. Design/methodology/approach Based on a semi-inductive approach, judgmental sampling was applied to select relevant health-care or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…The hospital can enhance the land value of the building by looking at the provided demand. It was found that communities contribute to the sustainability of the hospital [43]. Based on Table 9, building materials (f 1 ) with a weightage of 0.50710 is the most important criterion for redeveloping an abandoned airport, as rated by respondent 5.…”
Section: Best Alternative Selected By Respondentmentioning
confidence: 99%
“…The hospital can enhance the land value of the building by looking at the provided demand. It was found that communities contribute to the sustainability of the hospital [43]. Based on Table 9, building materials (f 1 ) with a weightage of 0.50710 is the most important criterion for redeveloping an abandoned airport, as rated by respondent 5.…”
Section: Best Alternative Selected By Respondentmentioning
confidence: 99%
“…In developing nations, the lack of flexibility, uncertainty of the economic environment, and the absence of institutional frameworks hinder the understanding of real issues within the supply chain, creating barriers to innovation [16]. Additionally, the growing demand for high-quality healthcare in developed countries has led to limited resources, making social marketing an effective tool for promoting sustainable behavioral change [41].…”
Section: Economic Sustainabilitymentioning
confidence: 99%
“…In sum, regarding the influence of hospital actions on sustainable development and sustainability, there are limited previous studies in the healthcare sector [3,4]. Principally, the little evidence that exists focuses on the management of both hospital waste and energy efficiency [55] Nevertheless, there are no previous studies focusing explicitly on desynchronization to reveal unsustainability in the healthcare industry, and that is our focus here.…”
Section: Sustainabilitymentioning
confidence: 99%
“…The literature does offer sustainability research in the healthcare sector [1][2][3][4][5]. However, no previous studies have examined the role of resource desynchronization in business model unsustainability within the healthcare sector, such as private hospitals.…”
Section: Introductionmentioning
confidence: 99%